Revitalizing the Srengseng City Forest as a sustainable ecotourism destination through the integrated landscape management approach - Silia Yuslim; Olivia Seanders; Anindita Ramadhani; Bagas Argya Syahbuhddin (Center for Science and Technology, Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
Srengseng City Forest in Jakarta has strong potential as an urban ecotourism. However, it faces several challenges, such as limited green infrastructure, insufficient educational facilities, low economic contribution, and inadequate institutional coordination. This study aims to evaluate its development potential and formulate a revitalization strategy based on ecotourism principles within an integrated landscape management (ILM) framework. Conducted from November 2024 to July 2025, the research applied a mixed-method approach combining quantitative descriptive analysis and qualitative inquiry. Data were collected through field observations, document review, Likert-scale questionnaires, and stakeholder discussions, involving 30 purposively selected respondents, including managers, residents, visitors, and experts. The assessment applied 30 indicators across six dimensions: environmental, infrastructure, community, economic, educational, and policy/institutional aspects. Quantitative data were analyzed using mean score classification, while qualitative data were examined thematically. The novelty of this study lies in the use of a multi-parameter evaluation framework incorporating urban ecotourism indicators adapted to local characteristics and integrated within the ILM concept. The results indicate very high ecological potential, especially in terms of biodiversity, but also highlight weaknesses in infrastructure, education, and economic aspects. Although policy support is relatively strong, implementation and stakeholder collaboration remain limited. Recommended strategies include improving eco-friendly facilities, strengthening conservation education, supporting local micro-enterprises, and establishing an ILM-based collaborative management forum.